Voice Search Technology: An Overview - Donepudi, Praveen Kumar (Engineering International, 2014)
Voice search technology is not new. It's been there since Audrey came out. But now it is increasing. People are using voice assistants, and so far 420 million voice assistants have been sold. This is growing rapidly because artificial intelligence integrated with voice search technology is more accurate and faster than text search. According to Google, its accuracy has improved to 95%. In short, it's an old technology that's gaining popularity with the rise of mobile phone voice assistants. In this study, the researcher has introduced different aspects and practical implications of voice search technology.
Keywords: Voice Search; Search Technology; Artificial Intelligence; Business Learning